The high-risk HPV E6 target scribble (hScrib) is required for HPV E6 expression in cervical tumour-derived cell lines - Kranjec, Christian (Papillomavirus Res, 2016)
The ability of high-risk HPV E6 oncoproteins to target cellular proteins which harbor PDZ domains is believed to play an important role in the virus life cycle and to influence the ability of these viruses to bring about malignant transformation. Whilst many of these PDZ proteins are potential tumour suppressors, involved in the control of cell polarity and cell-contact, recent studies suggest that mislocalisation or overexpression might result in the emergence of oncogenic functions. This has been shown most clearly for two E6 targets, hDlg and hScrib. In this study we show that hScrib plays such a role in HeLa cells, where its expression is required for maintaining high levels of HPV-18 E6 protein. Loss of hScrib has no effect on E6 stability but results in lower levels of E6 transcription and a reduced rate of E6 translation. We further show that, in the context of cervical tumour-derived cell lines, both hScrib and E6 cooperate in the activation of the S6 kinase signaling pathway, and thereby contribute towards maintaining high rates of protein translation. These results indicate that the residual hScrib that is present within HPV transformed cells is pro-oncogenic, and highlights the dual functions of E6 cell polarity targets.